1981
DOI: 10.1056/nejm198101223040402
|View full text |Cite
|
Sign up to set email alerts
|

Elastolytic Activity in Pulmonary Lavage Fluid from Patients with Adult Respiratory-Distress Syndrome

Abstract: To test the hypothesis that adult respiratory-distress syndrome (ARDS) is related to increased activity of the proteolytic enzyme elastase released from neutrophils in the lung, we determined the differential white-cell count, the elastolytic activity, the source of elastase, and the concentration and activity of the endogenous protease inhibitor alpha-1-antiprotease (alpha-1-AP) in bronchoalveolar lavage fluid from 23 patients with ARDS and from 55 patients without this syndrome. Neutrophil predominance (> 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
133
0
5

Year Published

1982
1982
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(148 citation statements)
references
References 18 publications
7
133
0
5
Order By: Relevance
“…The objective of this study was to elucidate the nature of cellular inflammatory response in the neonatal guinea pig lung and to determine whether elaboration of proteolytic enzymes into pulmonary effluent occurs in the immature or neonatal animal in a sequence similar to that found in adult animals and man. Both the chemotactic behavior of adult pulmonary inflammatory cells and their release of proteolytic enzymes injurious to lung tissue have been reported in adult respiratory distress syndrome (19), yet to our knowledge similar studies have not been re~orted in the " neonatal animal or human infant.…”
Section: Speculationmentioning
confidence: 81%
See 1 more Smart Citation
“…The objective of this study was to elucidate the nature of cellular inflammatory response in the neonatal guinea pig lung and to determine whether elaboration of proteolytic enzymes into pulmonary effluent occurs in the immature or neonatal animal in a sequence similar to that found in adult animals and man. Both the chemotactic behavior of adult pulmonary inflammatory cells and their release of proteolytic enzymes injurious to lung tissue have been reported in adult respiratory distress syndrome (19), yet to our knowledge similar studies have not been re~orted in the " neonatal animal or human infant.…”
Section: Speculationmentioning
confidence: 81%
“…Neutropenia induced with nitrogen mustard was shown to spare the lungs of oxygen-exposed adult rats to the effects described in control animals (28), suggesting that neutrophil mediated events caused these lesions in the adult animal. Lee et al (19) found elevated levels of neutrophilic elastase in the pulmonary lavage fluid of a majority of patients with adult respiratory distress syndrome, associated with increased numbers of leukocytes in pulmonary effluent in 20 of 23 patients. These workers have suggested that serine elastase proteolysis is the mechanism involved in the pathogenesis of the adult respiratory distress syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…For example, much of the neutrophil elastase recovered from the injured lung is complexed to endogenous inhibitors such as a1-antitrypsin or a2-macroglobulin and is not functional. [62][63][64][65][66][67] The balance between these destructive and protective compounds seems to be important in limiting tissue damage in ALI/ARDS. 68 Other potentially injurious products released by neutrophils include platelet activating factor (PAF) and arachidonic acid metabolites such as the leukotrienes.…”
Section: Epithelial Injurymentioning
confidence: 99%
“…There is now a growing body of evidence that HNE, like related serine proteases from primary granules, remains in large part bound to the external surface of the plasma membrane, where it cleaves biologically relevant and synthetic substrates (5). Released, free proteases become pre-eminent upon further activation and subsequent cell lysis, as in the expectorations of cystic fibrosis patients and those suffering from severe acute lung injury such as acute respiratory distress syndrome (6). However, the regulation of proteolytic activity at inflammatory sites under conditions of mild neutrophil-dependent inflammation mainly concerns membrane-bound serine proteases that are exposed at the cell surface after mobilization of their primary granules.…”
Section: H Uman Neutrophil Elastase (Hne)mentioning
confidence: 99%